The Role of Progesterone Receptors in Breast Cancer - Li Z; Wei H; Li S; Wu P; Mao X (Dove Medical Press, 2022)
Zhuo Li,1 Hongrui Wei,1 Siyan Li,1 Pei Wu,2 Xiaoyun Mao1 1Department of Breast Surgery, The First Affiliated Hospital of China Medical University, Shenyang City, Liaoning Province, People's Republic of China; 2Department of Surgical Oncology, The First Affiliated Hospital of China Medical University, Shenyang City, Liaoning Province, People's Republic of ChinaCorrespondence: Xiaoyun MaoDepartment of Breast Surgery, The First Affiliated Hospital of China Medical University, 155 Nanjing North Street, Heping District, Shenyang City, Liaoning Province, 110001, People's Republic of China, Tel/Fax +86 24 83282618, Email xymao@cmu.edu.cnAbstract: The progesterone receptor (PR) modulates estrogen receptors α (ERα) action in breast cancer; it is an upregulated target gene of ER, and its expression is dependent on estrogen. PR is also a valuable prognostic biomarker in breast cancer, especially in hormone-positive breast cancer. High expression of PR is more frequently observed in tumors with a better baseline prognosis (ie, luminal A) than tumors with a poor baseline prognosis (ie, luminal B). In the following review, we present the role of PR in breast cancer, including the genomic characteristics and pathways in breast cancer, PR and endocrine therapy.Keywords: progesterone receptor, breast cancer, endocrine therapy